2009
DOI: 10.1038/ijir.2009.58
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the acute effects of tadalafil on the cardiovascular system based on examination of serum oxidative status and paraoxonase activity in men with erectile dysfunction: a preliminary study

Abstract: Phosphodiesterase type 5 inhibitors were initially approved for the treatment of erectile dysfunction in men and were later suggested for some systemic disorders, mostly due to their possible beneficial effects on endothelial functions. Paradoxically, though, phosphodiesterase type 5 inhibitors may have some life-threatening effects, for which there is weak evidence, it appears that they are associated with cardiovascular problems such as myocardial infarction and stroke. This study aimed to investigate the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Verit et al [30] confirmed that tadalafil revealed a beneficial effect on the cardiovascular system by reducing serum levels of oxidative stress. It has also been demonstrated that oral administration of tadalafil (10 mg/kg) 2 h before a 30-min coronary artery occlusion results in a smaller infarct size (42 8 2%) compared with vehicletreated animals (54 8 3%; p = 0.01).…”
Section: Discussionmentioning
confidence: 73%
“…Verit et al [30] confirmed that tadalafil revealed a beneficial effect on the cardiovascular system by reducing serum levels of oxidative stress. It has also been demonstrated that oral administration of tadalafil (10 mg/kg) 2 h before a 30-min coronary artery occlusion results in a smaller infarct size (42 8 2%) compared with vehicletreated animals (54 8 3%; p = 0.01).…”
Section: Discussionmentioning
confidence: 73%
“…At peak blood levels following administration of 20 mg of tadalafil to men with ED, serum antioxidants rose 45%, serum oxidants declined 33% and serum paraoxonase-1 activity increased 50% (Figure 4, all Po0.0001). 68 The magnitude of increase of PON-1 was great enough to reverse the reduction of PON-1 observed in men with ED (inset, Figure 4). 3 This same dose given to men with cardiovascular risk factors caused a greater than twofold increase of FMD at the end of 4 weeks and continuing for 2 weeks after cessation of tadalafil (both Po0.01), whereas no changes were observed with placebo.…”
Section: Other Factorsmentioning
confidence: 88%
“…Further randomized trials are needed, Figure 4 In men with cardiovascular risk factors at 2 h after 20 mg of tadalafil, total serum antioxidant status (TAS) increased 45%, total serum oxidant status (TOS) decreased 33% and serum PON-1 activity increased 50% (all Po0.0001). 68 Inset: PON-1 activity was significantly decreased in men with ED (Po0.001). 3 Lifestyle, metabolism and erectile function DR Meldrum et al including various combinations of the listed interventions, 50 such as the favorable effects on ED of combining testosterone and sildenafil, 36 or of the Mediterranean diet, which increases intakes of omega-3's, antioxidants and folic acid.…”
Section: Reduction Of Inflammation Improves Endothelial Function and Edmentioning
confidence: 98%
“…Pharmacology attenuate doxorubicin-induced cardiotoxicity in patients [8], ischaemic/reperfusion injury in rat ovary [9] and decrease oxidative stress in erectile dysfunction in men [10]. Here, we report antioxidant and anti-inflammatory action of tadalafil in pulmonary hypertension induced by chronic hypobaric hypoxia in rat.…”
Section: Fundamental and Clinicalmentioning
confidence: 72%